Adjuvant External Beam Radiotherapy Following Enucleation of Eyes With Extraocular Extension From Uveal Melanoma. (May 2021) - Roelofs, Kelsey A.; Cohen, Victoria M.L.; Sagoo, Mandeep S.; Plowman, P. Nicholas; Negretti, Guy S.; O'Day, Roderick; Hay, Gordon; Arora, Amit K.; Damato, Bertil
Abstract : Purpose: To report local disease control and all-cause mortality in patients with extraocular extension (EOE) of uveal melanoma undergoing enucleation followed by observation or external beam radiotherapy (EBRT). Methods: Charts of patients enucleated between January 1, 1997 and December 31, 2019, with histopathological evidence of EOE of uveal melanoma were reviewed. Results: The cohort comprised 51 patients with a mean age of 67 ± 15 years, 22 (43%) of whom underwent adjuvant postenucleation EBRT. Risk factors for metastasis included presence of epithelioid cells (29/45; 88%), closed loops (20/43; 47%), monosomy 3 (16/25; 64%), and gain of 8q (20/22; 91%). Patients undergoing EBRT had more extensive EOE (median: 5.1 mm vs. 2.6 mm, p = 0.008) and surgical excision was less likely to be histologically complete (2/20; 10% vs. 14/25; 56%, p = 0.002). Local side effects following EBRT were seen in 64% (14/22). At latest follow up, 59% of patients (30/51) were alive, with a median follow up of 1.8 years (interquartile range: 2.9; range: 0.1–6.5]. By Kaplan-Meier survival analysis, the 5- and 10-year overall survival rates were 56% and 12%, respectively. There was no difference in all-cause mortality between those receiving adjuvant EBRT and those who were observed (log rank, p = 0.273). No cases of orbital recurrence were documented. Conclusions: Orbital EBRT causes significant morbidity. Cases with relatively small EOE undergoing enucleation can be safely observed, without adjuvant EBRT. Multicenter studies are required to better assess the role of EBRT when EOE is more extensive. Abstract : In 51 patients with extraocular extension of uveal melanoma undergoing enucleation, none developed clinically apparent orbital recurrence and no difference in all-cause mortality between observation versus adjuvant external beam radiotherapy was found.